The effect of a 4 week aerobic interval training block using maximal aerobic speed as the intensity measure with elite female hockey players - Heaney, N. (Journal of Australian Strength and Conditioning, 2012)
The aerobic energy system underpins team sport activities, and therefore, knowledge regarding training methods utilised to develop this energy system is essential. Such information can help direct training prescription and ensure that the most effective conditioning methods and principals are being utilised to obtain the desired aerobic adaptations. The purpose of this study was to assess the effectiveness of MAS guided interval training on eliciting improvements in aerobic fitness with elite females hockey players (n = 25, age = 22.3 ± 2.3 years, stature = 168.4 ± 7.6cm, mass = 61.8 ± 6.8kg). The girls were all Victorian Institute of Sport scholarship holders and were preparing to compete at the Australian Hockey League tournament. During this period they completed three MAS guided conditioning sessions per week. The YOYO IR1 was utilised to measure aerobic fitness and also, direct training intensity via the determination of maximal aerobic speeds. At the conclusion of the four week aerobic interval training block, there was an 18% improvement in YOYO IR1 total distance, with a team average of 1320m recorded at baseline and 1570m recorded at the conclusion of the intervention. In level and shuttle terms, the team average went from 16.6 at baseline to 17.3 at the conclusion of the intervention. Lastly, MAS improved by 0.5kmh, from 15.5kmh to 16kmh. In conclusion, MAS guided interval training is an effective training stimulus for eliciting aerobic energy system improvements in elite female hockey players.